LINC complex alterations in DMD and EDMD/CMT fibroblasts - Taranum, Surayya (Elsevier, 2012)
Emery-Dreifuss muscular dystrophy (EDMD) is a late onset-disease characterized by skeletal muscle wasting and heart defects with associated risk of sudden death. The autosomal dominant form of the disease is caused by mutations in the LMNA gene encoding LaminA and C, the X-linked form results from mutations in the gene encoding the inner nuclear membrane protein Emerin (STA). Both Emerin and LaminA/C interact with the nuclear envelope proteins Nesprin-1 and -2 and mutations in genes encoding C-terminal isoforms of Nesprin-1 and -2 have also been implicated in EDMD. Here we analyse primary fibroblasts from patients affected by either Duchenne muscular dystrophy (DMD) or Emery-Dreifuss muscular dystrophy/Charcot-Marie-Tooth syndrome (EDMD/CMT) that in addition to the disease causing mutations harbour mutations in the Nesprin-1 gene and in the SUN1 and SUN2 gene, respectively. SUN proteins together with the Nesprins form the core of the LINC complex which connects the nucleus with the cytoskeleton. The mutations are accompanied by changes in cell adhesion, cell migration, senescence, and stress response, as well as in nuclear shape and nuclear envelope composition which are changes characteristic for laminopathies. Our results point to a potential influence of mutations in components of the LINC complex on the clinical outcome and the molecular pathology in the patients.